Premium Type Fuel & Pertamax on the MT Ship. Long / P.1033 - Siswo Putro, Bhima; M. Nurdin; Nabila Ari Rahma Habibah (Dinasti Publisher, 2022)
Transport Loss is the depreciation of cargo caused by the journey from the loading port to the unloading port. The goal in shipping is to minimize the occurrence of transport loss. In achieving this goal, it can be found from the factors that influence the transport loss of cargo and how to minimize the occurrence of transport loss. The method used by researchers to overcome these problems is a qualitative descriptive method so that researchers can present the results of the research obtained. Data collection through documentation, observation and interviews. Interviews were conducted by researchers with the chief officer as the ship's party and the loading master as the land party, the researcher made direct observations on the MT ship. In length, the researcher also took documentation to support the validity of the research data. The results showed that the factors that cause transport loss are due to the lack of accuracy in measuring and calculating cargo, non-standard measuring instruments, differences in weather and evaporation. And the way to minimize transport loss is by carrying out loading and unloading in accordance with procedures, calibrating measuring instruments and carrying out maintenance on loading and unloading suggestions. From the research results it can be concluded that transport loss is caused by several factors that must be minimized to the tolerance limit that has been determined by a shipping company. And the way to minimize transport loss is by carrying out loading and unloading in accordance with procedures, calibrating measuring instruments and carrying out maintenance on loading and unloading suggestions. From the research results it can be concluded that transport loss is caused by several factors that must be minimized to the tolerance limit that has been determined by a shipping company. And the way to minimize transport loss is by carrying out loading and unloading in accordance with procedures, calibrating measuring instruments and carrying out maintenance on loading and unloading suggestions. From the research results it can be concluded that transport loss is caused by several factors that must be minimized to the tolerance limit that has been determined by a shipping company.